Thermal Analysis of Kirloskar VCR Engines Using Blended Biodiesels under Varying Loads - Shiwangi Mishra; Vivek Gedam (International Journal of Electrical and Communication Engineering Technology, 2025)
The increasing demand for sustainable energy has prompted much research into environment-friendly substitutes for traditional fossil fuels. In this study, the thermal performance and emission characteristics of Kirloskar Variable Compression Ratio (VCR) diesel engines evaluated with varying load conditions using biodiesel-sourced oil blended with soybean oil are discussed. B0 (pure diesel) to B100 (pure biodiesel) blends were considered for the study to assess their effects on parameters, like brake thermal efficiency (BTE), brake specific fuel consumption (BSFC), carbon dioxide (CO₂), sulfur dioxide (SO₂), nitrogen oxides (NOₓ), and particulate matter (PM) emissions. The experimental findings indicated that biodiesel blends contributed to enhanced combustion temperatures and flow of exhaust gases while still providing an acceptable efficiency level under load conditions. Significantly reduced CO₂ and PM emissions were also observed for B20 with respect to pure diesel, indicating its ability to act as a cleaner fuel alternative. Although small differentials in efficiency showed up between blends, B20 gave a fair balance between performance and environmental merits. The study closes with the contention that low concentrations, such as B20, can easily be used in existing diesel engines with no major modifications for betterment of the environment while at the same time allowing the engine to perform at its best longevity with reliability. This will increase the uptake of biodiesel as a possible alternative. Methods of analysing engine fuel, performance metrics, and efforts concerning pilot and biodiesel usage, use of different blends, test implementations, and emissions observed will be covered. In addition, the potential of biodiesel for adoption in each area will be reviewed based on input from other countries. Finally, in another section of the final report, formulation criteria will be reviewed at the biodiesel plant.
Keywords: Soybean oil; Variable Compression Ratio (VCR); biodiesel; brake specific fuel consumption (BSFC); brake thermal efficiency (BTE)